Tam-giao cultural expression and representations of post-war trauma in Vietnamese visual arts - Le, Kim Thu (Curtin University, 2015)
This study identifies Tam-giao, a combination of three philosophies, Buddhism, Taoism and Confucianism whose use is reflected in Vietnamese visual arts, and examines the role of Tam-giao in Vietnamese post war art since 1975. The research contextualizes interviews with Vietnamese artists who use post traumatic themes in their artworks, revealing how Tam-giao cultural expression reflects individual and communal concerns. The forms of post war trauma are codified and illustrated through artistic case studies.